Compartment no. 6 [videorecording (DVD)] - Haarla, Seidi; Borisov, I͡Uriĭ, 1992-; Drukarova, Dinara; Aug, I͡Ulii͡a, 1970-; Kostina, Lidia; Alatalo, Tomi; Liksom, Rosa (Sony Pictures Home Entertainment, 2022)
A young Finnish woman escapes an enigmatic love affair in Moscow by boarding a train to the arctic port of Murmansk. Forced to share the long ride and a tiny sleeping car with a larger than life Russian miner, the unexpected encounter leads the occupants of Compartment No. 6 to face major truths about human connection.